Factors affecting individual career management among undergraduates in higher education institutions - Wong, Siew Chin; Quek, Lor Shen (Human Resource Management Academic Research Society, 2015)
This research aims to examine the factors that affect undergraduates’ perception towards career management in Malaysia’s higher education institutions. A correlation study was conducted in 16 private higher education institutions. Samples of 150 undergraduates were involved in this study. The findings suggest that individual-related factors (self-efficacy and outcome expectations) and social-related factor (peer influences) have positive relationship with individual career management. The research findings are useful to organizations (i.e., potential employers) to have better understanding towards career management trends among undergraduates who are the potential employees to join the labor market upon graduation. The appropriate Human Resource Development interventions should be implemented to support their career planning and development in the future.